Cellular and molecular mechanisms in graft‐versus‐host disease. Issue 2 (7th December 2015) - Zhang, Lingling; Chu, Jianhong; Yu, Jianhua; Wei, Wei
Abstract : Review of how immune cells and molecules are implicated in the physiopathology of GVHD, a complication in patients undergoing HSCT. Abstract : Graft‐versus‐host disease is a complication in patients undergoing hematopoietic stem cell transplantation. Graft‐versus‐host disease includes acute graft‐versus‐host disease and chronic graft‐versus‐host disease. Host APCs (e.g., dendritic cells and macrophages), effector T cells (e.g., Th1, Th17, and abnormal Th17:regulatory T cell ratio), B cells, and NK cells are implicated in graft‐versus‐host disease physiopathology. Proinflammation cytokines (e.g., IL‐17, IL‐1β, and TNF‐α) are increased in graft‐versus‐host disease. Costimulatory molecules play an important role in inducing graft‐versus‐host disease. Pattern‐recognition receptors, such as TLRs and nucleotide‐binding oligomerization domain‐like receptors, are critically involved in the pathogenesis of graft‐versus‐host disease. Complement system C3 mediates Th1/Th17 polarization in human T cell activation and skin graft‐versus‐host disease. Accumulation of CD26 T cells in graft‐versus‐host disease target organs was found. As a therapeutic target, soluble CD83 molecules or antibodies have been demonstrated to have therapeutic effects against graft‐versus‐host disease, and signaling molecules promote the inflammatory and immune process of graft‐versus‐host disease. These immune cells and molecules could be the predictors of graft‐versus‐host disease development and the drug targets of the treatments for graft‐versus‐host disease. This article focuses on major advances on cellular and molecular mechanisms in graft‐versus‐host disease.